SUPPLY CHAIN PERFORMANCE DAN KINERJA PERUSAHAN - Seto Sulaksono Adi Wibowo; Aditya Wirangga (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2019)
This study aims to examine the effect of supply chain performance on firm performance. Supply chain performance is proxyed using inventory turnover and days of supply as independent variables, while company performance is proxyed using the net profit margin as the dependent variable. This research use manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2016 period as samples. The purposive sampling method is used to matches the sample criteria. The analysis technique used in this study is multiple regression analysis using the t test. The results of the study found that the inventory turnover variable has a positive influence on company performance, while the days of supply variable has a negative influence on company performance.